Bulgaria and Russia of the early 20th century: from the correspondence of N. S. Derzhavin with Bulgarian scientists - Vartanyan, Egnara G. (Journal of the Belarusian State University. History, 2024)
Some plots from the epistolary heritage of the Russian scientist-slavist N. S. Derzhavin are given, in particular excerpts from his correspondence with famous Bulgarian scientists I. D. Shishmanov and V. N. Zlatarski. Through the prism of the scientist’s letters, the socio-political situation in Russia and Bulgaria at the beginning of the 20th century is shown. The article examines N. S. Derzhavin’s reaction to the events at Sofia University in 1907, as well as his response to events such as the October Revolution in Russia, the Balkan Wars and the World War I. The versatile administrative, pedagogical and research activities of the scientist are described. The methodological basis of the work is the scientific principles of historicism and objectivity. Historical-genetic, historical-chronological and narrative research methods are used. The use of the civilizational approach in the article is due to the need to study the events of the past in the human dimension, the importance of man in the development of civilisation. It is concluded that N. S. Derzhavin was an ambiguous personality, however, he possessed undoubted talent and made a great contribution to the development of Russian Slavic studies.
Keywords: N. S. Derzhavin; Bulgaria; Russia; scientists; correspondence; university; Bulgarian Academy of Sciences; Slavonic studies